Tissue distribution, metabolism and hepatic tissue injury in Chinese lizards (Eremias argus) after a single oral administration of lambda-cyhalothrin. (November 2016) - Chang, Jing; Li, Jitong; Wang, Huili; Wang, Yinghuan; Guo, Baoyuan; Yin, Jing; Hao, Weiyu; Li, Wei; Li, Jianzhong; Xu, Peng
Abstract: Lambda-cyhalothrin (LCT) is a widely used pyrethroid with neurotoxicity. However, little is known about the toxicokinetics of LCT in reptiles. In this study, the absorption, distribution, metabolism and excretion of LCT in Chinese lizards ( Eremias Argus ) were determined following a single dose (10 mg kg −1 ) treatment. In the liver, brain, gonads and skin, LCT levels peaked within several hours and then decreased rapidly. However, the concentration of LCT gradually increased in the fat tissue. More than 90% of the LCT dose was excreted in the faeces. One LCT metabolite, 3-phenoxybenzoic acid (PBA), was detected in lizard plasma and tissues. PBA preferentially accumulates in the brain and plasma. The half-life of PBA in the brain was 3.2 days, which was 35.4-fold greater than that of LCT. In the plasma, the concentration of PBA was significantly higher than that of LCT. The bioaccumulation of LCT in tissues was enantioselective, and the enantiomeric fractions (EF) ranged from 0.72 to 0.26. The preferential accumulation of enantiomers changed according to exposure time, but the reasons behind this phenomenon were not clear. For pathological analysis, vacuolation of the cytoplasm and large areas of necrosis were observed in the liver sections after 168 h of dosing. The liver tissues exhibited both decreases in the hepatosomatic index and histopathological lesions during the exposure period. In this study, the effect concentration of LCT in lizards was 200-fold lower than its LD50 value used in risk assessments for birds. These results may provide additional information for the risk assessment of LCT for reptiles and indicate that birds may not be an ideal surrogate for reptile toxicity evaluation. Graphical abstract: Highlights: Rapidly elimination of LCT in lizard tissues except for the fat. PBA preferentially accumulated in the brain and skin through blood circulation. LCT in the tissues was enantioselective and the EF values ranged from 0.72 to 0.26. Liver was more vulnerable according to the HSI change and histopathological lesions. Abstract : LCT was quickly eliminated from lizard tissues within several hours and accumulated gradually in the fat, whereas its metabolite, PBA, accumulated in the brain and skin.